Operation research Quantitative analysis for management - Chawla, K K; Gupta, Vijay; Sharma, Bhushan K. (New Delhi Kalyani Publishers, 2020)
Introduction to operations research; linear programming problems; linear programming problems; network analysis; pert and cpm; inventory control; decision theory; queuing theory; dynamic programming problem; simulation; game theory; sequencing problems; revised simplex method.
Keywords: Operation Research